The analysis of implementation and scoring for KSSM oral assessment among the lower secondary teachers - Said, Rozita Radhiah; Jamil, Halimah (Human Resource Management Academic Research Society, 2021)
The Standards-Based Curriculum for Secondary School (KSSM) was first implemented in Malaysia in 2012 by applying an assessment system integrated with the teaching and learning process (T&L) to replace the previous education system that was more examination-oriented. The Curriculum and Assessment Standard Document (DSKP) for the Malay Language subject was introduced in April 2016 and implemented by stages from 2017 until now. Thus, after three years, this study attempts to analyse the implementation and scoring procedures of oral assessment integrated with teaching and learning in the classroom among the seven lower secondary school teachers from a district in Negeri Sembilan. Two participants were selected to represent each school in different categories which are Sekolah Menengah Kebangsaan (SMK), Sekolah Agama Bantuan Kerajaan (SABK) and Sekolah Berprestasi Tinggi (SBP). Qualitative research with a case study design has been conducted on seven Malay Language teachers between 26 to 52 years old. They were selected through purposive sampling. The research data were collected by triangulation, through the interview method, observation on the implementation of oral assessment for teaching and learning (T&L) in the classroom, and document analysis. The collected data were analysed using the ATLAS.ti software version 8. The main findings of the study showed that all participants successfully implemented the assessment based on DSKP. However, the oral scoring procedure should still be emphasized and monitored because three out of seven Malay Language teachers did not enforce it using a proper process. In general, this study found that the teachers successfully integrated the theory of the function, the role of classroom assessment, and the steps outlined by the Ministry of Education (MoE), starting from the planning procedure, selecting methods, implementing, recording, follow-up action, and reporting the assessment. Recommendations for future studies related to scoring consistency, rubric appropriateness, reporting, and assessment quality monitoring need to be enforced in every assessment aspect to make sure it is in parallel which results are complementary and high accountability of the assessment.